Overview Of Teaching Skills Tutor Package C Mathematics Subjects Non-Formal Education Unit Learning Activities In Pariaman City - Novita Syahli, Vivi; Sunarti, Vevi (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This research is motivated by the lack of skilled human resources in the ongoing implementation of the SKB. UPT SKB Pariaman requires skilled and supportive human resources to be able to implement existing programs. This research aims (1) To see a picture of the Tutor's questioning skills in reviewing previous learning (2) To see a picture of the Tutor's skills in providing verbal and non-verbal reinforcement (3) To see a picture of the Tutor's explaining skills in providing new material (4) To see overview of the Tutor's skills in opening and closing the lesson (5) To see an overview of the Tutor's skills in guiding small group discussions. This research is quantitative research with a descriptive type. In this study, a population of 38 people was used and the research sample was 38 residents studying at the learning activity studio in Pariaman City using the Total Sampling sampling technique. The analysis in this research is descriptive. The results of this research show that (1) The description of the Tutor's questioning skills in reviewing previous learning is categorized as very high (2) The description of the Tutor's skills in providing verbal and non-verbal reinforcement is categorized as high (3) The description of the Tutor's explaining skills in providing new material is categorized as high (4 ) Description of the Tutor's skills in opening and closing the lesson is categorized as high (5) Description of the Tutor's skills in guiding small group discussions is categorized as high Keywords: Tutor Teaching Skills, Package C, Mathematics Subjects